DOP10 Early intestinal resection in Crohn's Disease is not associated with severe long-term disease course. (30th January 2023) - Grellier, N; Kirchgesner, J; Uzzan, M; Mclellan, P; Stefanescu, C; Lefèvre, J H; Panis, Y; Sokol, H; Beaugerie, L; Treton, X; Seksik, P
Abstract: Background: Crohn's Disease patients (CD) with early complicated behaviour (stenosis and/or fistula) are thought to have a more severe long-term disease course. To address this question, we focused on ileal CD that requires early intestinal resection after diagnosis. We aimed to assess the impact of the time to surgery from diagnosis on the risk of severe disease course in patients with ileal CD undergoing a primary ileocecal resection (ICR) or ileal resection (IR). Methods: All CD patients who underwent ICR or IR between January 2001 and December 2015 and followed in two Inflammatory Bowel Disease (IBD) tertiary centres in France were included. Data were retrieved using dedicated IBD database and patients' medical records. Early resection was defined as a surgery performed within 6 months after diagnosis. Two control groups with patients who underwent the first surgery between 6 months and 2 years and between 2 and 5 years after diagnosis were enrolled. The primary outcome was second intestinal resection. Secondary outcomes included the need for biologic treatments after initial intestinal surgery. Patients were followed from the date of first surgery until September 2022. Kaplan Meier survival analysis and log-rank test were used to estimate the survival without second intestinal resection and biologic initiation according to the time of first intestinal resection to diagnosis. Results: Among 404 patients who underwent ICR or IR within 5 years after diagnosis, 130 (32.2%) patients had undergone surgery within 6 months after diagnosis (Group A), 138 (34.2%) patients between 6 months and 2 years (Group B) and 136 (33.7%) patients between 2 and 5 years (Group C). Clinical data are shown in Table 1. The cumulative risk of a second ICR or IR ten years after the first surgery was 25.2% (95% CI 12.5 - 40.2) in group A, 16.6% (5.1 - 33.9) in group B and 22.8% (9.8 – 39.1) in group C, without statistically significant difference (p = 0.25) (Figure 1). The risk of biological exposure after the first surgery was not significantly different in the three groups (p = 0.12) (Figure 2). The cumulative risk to start a biologic therapy at ten years was 46.2% (35.0 – 56.6) in group A, 39.0% (26.2 – 51.5) in group B and 48.0% (36.3 – 58.8) in group C. Conclusion: In a bicentric cohort with long-term follow-up, intestinal resection within 6 months of CD diagnosis was not associated with an increased risk of second surgery as compared to patients with primary ICR/IR later after diagnosis. Furthermore, patients with early intestinal resection did not need more biological therapies after the first surgery. These data suggest that early intestinal resection in CD is not a predictor of poor long-term prognosis compared to late resection.